Integrating GLAM principles in the development of UM Special Collections - Achmad Qorni Novianto; Nurenzia Yannuar; Raden Sapto Wibowo; Aa Kosasih; Indah Wahyu Puji Utami; Khairulbahiyah Binti Yaakub (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. This study explores developing a GLAM-based Special Collection at UM to preserve the history of UM and Malang. This research question is (1) how can the GLAM framework be applied effectively to the development of UM Special Collection (2) challenges and obstacles in the implementation process. Complementing GLAM studies in national and regional libraries, this research applies it to academic libraries. Research Methods. Using R&D and qualitative descriptive methods, the studies followed four stages: needs analysis, planning, implementation, and evaluation. Data were collected through FGDs, observations, and interviews with retired librarians. Data Analysis. The needs analysis data were qualitatively analyzed for planning and implementation. Interview results were thematically analyzed to support collection organization and exhibition text development, while FGDs were used to evaluate progress and refine the final presentation of the collection. Results. The findings indicate that the GLAM framework effectively curateshistorical collections in academic settings, supported by the use of digital technology to develop digital galleries and organize collections. Conclusion. This study concludes that GLAM principles can be applied in academic libraries to enhance the visibility and sustainability of historical collections. At the same time future research may explore the impact of Special Collections.